Motives for and Barriers to Physical Activity in Twin Pairs Discordant for Leisure Time Physical Activity for 30 Years - Aaltonen, S.; Leskinen, T.; Morris, T.; Alen, M.; Kaprio, J.; Liukkonen, J.; Kujala, U. (International Journal of Sports Medicine, 2012)
Long-term persistent physical activity is important in the prevention of chronic diseases, but a large number of people do not participate in physical activity to obtain health benefits. The purpose of this study was to examine the motives and perceived barriers to long-term engagement in leisure time physical activity. Same-sex twin pairs (N=16, mean age 60) discordant for physical activity over 30 years were identified from the Finnish Twin Cohort. We evaluated participants’ physical activity motivation with the 73-item Recreational Exercise Motivation Measure and assessed barriers to physical activity with a 25-item questionnaire. The characteristics of physical activity motivation and perceived barriers between the active and inactive co-twins were analysed using paired tests. Motives related to the sub-dimensions of enjoyment and physical fitness and psychological state were the most important reasons for participation in physical activity among all the twin individuals analysed. The sub-dimensions mastery (p=0.018, Cohen’s d=0.76), physical fitness (p=0.029, Cohen’s d=0.69), and psychological state (p=0.039, Cohen’s d=0.65) differed significantly between active and inactive co-twins. More than half of the participants reported no reasons for not being physically active. If reasons existed, participation in physical activity was deterred mostly by pain and various health problems. This study found no differences in perceived barriers between active and inactive co-twins. We conclude from our results that the main factors promoting persistent leisure time physical activity were participants’ wish to improve or maintain their physical skills or techniques, a feeling that exercise would improve their mental and physical health and that they found the activity enjoyable. This study helps us understand the importance of the role of motives and the minor role of perceived barriers for engagement in persistent physical activity.
Keywords: motivation; perceived barrier; physical activity; twin study